A qualitative approach to study the perception of job seekers towards digital job portals. (13th September 2022) - Sarath, C.; Sandhya, G.
The rising technological changes in this digital era have led to impact various genres, both in academia and practice. Recruitment through online mode has become the new norm for sourcing the right skill and talent. Thus, it is necessary to study how the job seekers perceive online job search platforms. To satisfy job seekers' requirements and to be competitive in the market, the job portals have to understand the perception of their potential job seekers. The purpose of this paper is to understand the perception of job seekers towards digital job portals. With this premise, the perception of job seekers towards multiple job portals has been examined based on five dimensions: trustworthiness, website aesthetics, service, cost-effectiveness, and content. Except for the dimensions 'cost-effectiveness' and 'content' which evolved out of this qualitative investigation, all the other above-mentioned dimensions did seem to have corroborations with the literature and various other research studies conducted in other Asian economies.